The Effect of Toothpastes Containing Natural Extracts on Bacterial Species of a Microcosm Biofilm and on Enamel Caries Development - Braga, Aline Silva; Abdelbary, Mohamed Mostafa Hefny; Kim, Rafaela Ricci; de Melo, Fernanda Pereira de Souza Rosa [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Dokkedal, Anne Lígia [UNESP]; Conrads, Georg; Esteves-Oliveira, Marcella; Magalhães, Ana Carolina (MDPI, 2022)
This study investigated the effects of herbal toothpaste on bacterial counts and enamel demineralization. Thirty-six bovine enamel samples were exposed to a microcosm biofilm using human saliva and McBain saliva (0.2% sucrose) for 5 days at 37 °C and first incubated anaerobically, then aerobically–capnophilically. The following experimental toothpaste slurries (2 × 2 min/day) were applied: (1) Vochysia tucanorum (10 mg/g); (2) Myrcia bella (5 mg/g); (3) Matricaria chamomilla (80 mg/g); (4) Myrrha and propolis toothpaste (commercial); (5) fluoride (F) and triclosan (1450 ppm F), 0.3% triclosan and sorbitol (Colgate®, positive control); (6) placebo (negative control). The pH of the medium was measured, bacteria were analyzed using quantitative polymerase chain reaction, and enamel demineralization was quantified using transverse microradiography. The total bacterial count was reduced by toothpaste containing Myrcia bella, Matricaria chamomilla, fluoride, and triclosan (commercial) compared to the placebo. As far as assessable, Myrcia bella, Matricaria chamomilla, and Myrrha and propolis (commercial) inhibited the outgrowth of S. mutans, while Lactobacillus spp. were reduced/eliminated by all toothpastes except Vochysia tucanorum. Mineral loss and lesion depth were significantly reduced by all toothpastes (total: 1423.6 ± 115.2 vol% × μm; 57.3 ± 9.8 μm) compared to the placebo (2420.0 ± 626.0 vol% × μm; 108.9 ± 21.17 μm). Herbal toothpastes were able to reduce enamel demineralization.
Keywords: antimicrobial strategies; dental caries; oral biofilms; plants